Non-Coding RNAs in Neural Networks, REST-Assured - ROSSBACH, Michael (Frontiers in Genetics, 2011)
In the nervous system, several key steps in cellular complexity and development are regulated by non-coding RNAs (ncRNAs) and the repressor element-1 silencing transcription factor/neuron-restrictive silencing factor (REST/NRSF). REST recruits gene regulatory complexes to regulatory sequences, among them the repressor element-1/neuron restrictive silencer element (RE1/NRSE), and mediates developmental stage-specific gene expression or repression, chromatin (re-)orga-nization or silencing for protein-coding genes as well as for several ncRNAs like microRNAs (miRNAs), short interfering RNAs (siRNAs) or long ncRNAs. NcRNAs are far from being just transcriptional noise and are involved in chromatin accessibility, transcription and post-transcriptional processing, trafficking or RNA editing. REST and its cofactor CoREST are both highly regulated through various ncRNAs. The importance of the correct regulation within the ncRNA network, the ncRNAome, is demonstrated when it comes to a deregulation of REST and/or ncRNAs associated with molecular pathophysiology underlying diverse disorders including neurodegenerative diseases or brain tumors.